Impact Study of Community’s Nursery Program on Land Cover Change in Jembrana Regency, Bali - Erna Rosita; M. Sani Roychansyah (Balai Penelitian dan Pengembangan Lingkungan Hidup dan Kehutanan Makassar, 2020)
One of the priority activities in Forest and Land Rehabilitation (FLR) program conducted by the Ministry of Environment and Forestry since 2010 is People’s Nursery Program/Kebun Bibit Rakyat (KBR). Jembrana Regency as one of the districts that participated in this program is an area with a diverse physical conditions and represents each watershed zone consisting of upstream, middle, and downstream, so it becomes interesting to study. This study aims to describe the KBR program in terms of changes in land use at the KBR location. The method used in this research was a qualitative descriptive approach referring to data on changes in land cover in 2009, 2013, and 2016 as an analysis material that represents the year before the program, the year when the program began, and the year when the program was harvested. The results of the study showed that there was a change in land cover at the locations during the implementation of the KBR program in Jembrana Regency, namely an increase in dry land forest area of 44.2 ha and mixed gardens of 252.5 ha. This shows that the KBR program has contributed to the RHL program in terms of increasing the area of vegetation and has involved the community in its implementation.